Hydrozetes species (Acari, Oribatida) at bog ponds and pools in the Tatra National Park and Orawa-Nowy Targ Basin (Kotlina Orawsko-Nowotarska) in southern Poland - Mistrzak, Marcin; Seniczak, Anna; Seniczak, Stanisław (Biological Letters, 2012)
The Hydrozetes fauna was investigated at the edges of 4 ponds and pools with acid water in southern Poland. Mites of this genus achieved the highest mean abundance (6x104 ind./m2) at a pond in the Tatra National Park (Staw Toporowy Niżni; pH = 3.9; 1089 m a.s.l.). H. confervae dominated there (98%), accompanied by H. octosetosus and H. lacustris. The same species were also present at a nearby pond (Staw Toporowy Wyżni; pH 3.9; 1120 m a.s.l.), but in significantly lower numbers. In the bogs of the Orawa-Nowy Targ Basin, at the edge of pool in Kaczmarka (pH 3.6; 650 m a.s.l.), H. lacustris and H. octosetosus were present, and the former species dominated (73%). The latter species is interesting, because it was not recorded in Europe until recently. At the other pool, in Łysa Puścizna (pH 4.5; 650 m a.s.l.), only H. lacustris was present. The lower abundance and species richness of Hydrozetes at the bog pools in the Orawa-Nowy-Targ Basin, in comparison to the Tatra National Park, was probably caused by poorer water conditions, due to more advanced succession, peat exploitation and disturbed water conditions in the Basin.